AKAD QARDH DALAM LEMBAGA KEUANGAN SYARIAH - fasiha fasiha (Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2018)
Financial institutions involved in fund management. like, Islamic banking that provides a wide range of products offered to people. This paper will explore one product of Islamic financial institutions that is Qardh. This understanding begins with the Implementation of Qardh Agreement at Sharia Financial Institutions. The results show that the implementation of the contract in the LKS should be in accordance with the terms and conditions of qardh, qardh contract and shigat qardh. LKS as a container in channeling public funds. Such as: zakat, infaq, and shadaqah in Qard form. Qard is a non-profit loan. LKS provides eligibility to customers. LKS should does not gain any profit in the contract. In qard, the customer returns the loan in accordance with the loan amount to the LKS